Effective breastfeeding practices among mothers exclusively breastfeeding infants in Ethiopia - Yonas Abebe; Beriso Dadi (Clinical Epidemiology and Global Health)
Background: Effective breastfeeding is crucial for infant well-being, yet less than half of infants globally receive recommended practices. Ethiopia faces high infant mortality linked to malnutrition and ineffective breastfeeding. This study aimed to determine the prevalence of effective breastfeeding and identify factors associated with its practice among mothers who exclusively breastfeed. Methods: A facility-based, cross-sectional study design was employed. This study was conducted among 414 mothers at Dilla University Referral Hospital from July 1 to September 30, 2023. Participants were selected using systematic random sampling. Data were collected using an interviewer-administered questionnaire and an observational checklist. The collected data were entered into Epi-Data version 4.2 and exported to SPSS version 26 for analysis. Bivariate and multivariable binary logistic regression analyses were used to investigate the associations between variables. Result: The prevalence of effective breastfeeding practice was 23 % (95 % CI: 18.5, 26.8). In the multivariable binary logistic analysis, postpartum counselling (AOR = 2.61; 95 % CI 1.27, 5.39), breastfeeding experience (AOR = 6.08; 95 % CI 1.34, 27.39), postpartum breastfeeding demonstration (AOR = 4.14; 95 % CI 1.13, 15.2) and attending four or more antenatal care visits (AOR = 4.41; 95 % CI 2.3, 8.35) were factors significantly associated with effective breastfeeding practice. Conclusion: Effective breastfeeding is unacceptably low among study participants. To increase effective breast-feeding practice, counselling during health service utilization visit and demonstrating breastfeeding techniques before discharge from the health facility are recommended measures to be taken.